The Role of The Environment as a Source of Geography Learning on The Spatial Thinking of Grade X Students at SMA BK Palu - Gesadombu, Reilda Meigita; Listiqowati, Ika; Hasan, Haslita Rahmawati; Arsy, Risma Fadhila (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
This study aims to determine the role of the environment as a source of geography learning on the spatial thinking of tenth-grade students at SMA BK Palu. Quantitative descriptive research is an approach that was implemented in this study, with a total of 61 students consisting of 25 students from class XA, 21 students from class XB, and 15 students from class XC, who were used as research subjects. Data collection was conducted through tests, observations, and limited interviews. The research instruments consisted of an objective multiple-choice test with 15 questions on spatial thinking indicators, observations to determine the learning process in the classroom, and interviews with students about the use of the environment as a learning resource. The results indicate that the spatial thinking abilities of students in classes XA and XB are better than those in class X C. This can be seen from the dominance of students in the good and very good categories in classes XA and The results of the observation also indicate that learning in classes XA and XB has linked the material to the surrounding environment while in class XC the use of the environment as a learning resource has not been optimal. In addition the interview results indicated that the material will be easier for students to understand when learning is linked to the surrounding environment. The study concluded that the role of the environment as a source of geography learning for spatial thinking among tenth grade students at SMA BK Palu has not been applied even across classes. It is recommended that teachers consistently improve the implementation of environment-based learning and that future researchers develop similar studies in different learning contexts.